Di Balik Ketebelakangan Kongo: Pengaruh Huayou Cobalt dalam Kerjasama Pertambangan Kongo dan Tiongkok - Denta Utama; Mohamad Rosyidin; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The Democratic Republic of the Congo is a country with abundant cobalt resources, but this does not then provide economic stability to the Congo. China uses this through its transnational company Huayou Cobalt to secure the cobalt supply in the Congo by creating a cooperation project between the two by bartering mining rights and investing funds for infrastructure development. It is feared that this will lead to Congo's dependence on China's financial capacity to advance their country. This research uses neo-marxism theory with further research using dependency theory by Gunder Frank. The author collects data using the literature study method through journals/articles, books, websites, and international news. This research is explanatory, which will provide an overview of why the Congo cannot get out of adversity and dependence on direct investment provided by China by exchanging mining rights with China. The result of this study is that Congo is trapped in a cycle of dependence due to the unequal international structure and the Congo's inability to deal with its domestic problems.Keywords: Huayou Cobalt, Democratic Republic of Congo, investment, exploitation, dependence.